Development Framework of Emergency Call Application in Pregnant Women - Antono Suryoputro; Rani Tiyas Budiyanti (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
Referral problems in high-risk pregnancy can increase pregnant woman mortality. Beside of referral's delay in an emergency case, delay in knowing the danger sign also be the problem. In the development of technology, many information systems can be applied to recognize the danger signs of pregnancy and request immediate help in an emergency case. One of them is using the application on the smartphone. This study aims to develop a framework of emergency call application in pregnant women. This study was literature review research from the journal year 2009-2019, book, proceeding that related to danger signs of pregnancy and emergency call apss in pregnant women. Time research was done in July until Agustus 2019. The Result is a development framework of emergency call application in pregnant woman consists of personal information, danger sign information, calculator prediction of risk pregnancy, emergency button, chat feature, and examination history. It needs to identify health professionals, health care, and family that can be contacted immediately. The Conclusion is To implement an emergency system application for pregnant women, good technology literacy and joint commitments are needed.